2021
DOI: 10.1136/bmjgh-2021-007051
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties faced by older Rohingya (forcibly displaced Myanmar nationals) adults in accessing medical services amid the COVID-19 pandemic in Bangladesh

Abstract: BackgroundCOVID-19 has seriously disrupted health services in many countries including Bangladesh. This research aimed to explore whether Rohingya (forcefully displaced Myanmar nationals) older adults in Bangladesh faced difficulties accessing medicines and routine medical care services amid this pandemic.MethodsThis cross-sectional study was conducted among 416 Rohingya older adults aged 60 years and above residing in Rohingya refugee camps situated in the Cox’s Bazar district of Bangladesh and was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 46 publications
3
13
0
Order By: Relevance
“…This study reported a very high prevalence of COVID-19-related anxiety and perceived stress (68% and 93% respectively) among the older adults residing in the Rohingya refugee camp. Poor-socioeconomic conditions, previous traumatic experiences, ongoing risks in their life, uncertainties, and poor access to health care services during the COVID-19 pandemic might have resulted higher level of COVID-19-related anxiety and perceived stress among the participants (Limon et al, 2020 ; Mistry et al, 2021b , c ). We did not find any study conducted in the refugee settings exploring COVID-19 related anxiety and stress using the scales used in the current study to compare with.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study reported a very high prevalence of COVID-19-related anxiety and perceived stress (68% and 93% respectively) among the older adults residing in the Rohingya refugee camp. Poor-socioeconomic conditions, previous traumatic experiences, ongoing risks in their life, uncertainties, and poor access to health care services during the COVID-19 pandemic might have resulted higher level of COVID-19-related anxiety and perceived stress among the participants (Limon et al, 2020 ; Mistry et al, 2021b , c ). We did not find any study conducted in the refugee settings exploring COVID-19 related anxiety and stress using the scales used in the current study to compare with.…”
Section: Discussionmentioning
confidence: 99%
“…Immediate partner could play a crucial role providing mental support to the fellow partner, particularly during an emergency like COVID-19 pandemic when the support from outside is limited (Jiang et al, 2022 ; Vowels et al, 2021 ). In absence of the partner, the participants would have found it difficult to deal with their emotions related to the overwhelming fear associated with COIVD-19 pandemic (Mistry et al, 2021a , b , c , d ; Quadros et al, 2021 ), resulting higher level of COVID-19-related anxiety and perceived stress. We also found that COVID-19-related anxiety and perceived stress was significantly higher among the participants who were feeling concerned/overwhelmed by COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, over 1.3 million Rohingya refugees are living in highly congested camps with high risk of Covid-19 in Bangladesh (Khan & Ors 2021;Mistry & Ors 2021). The majority of the displaced Rohingya population live in 34 camps with poor access to water and sanitation, and very limited health services (UN High Commissioner for Refugees (UNHCR) 2021a).…”
Section: [E] Out Of Sight Out Of Mind: Forced Displacement and Covid-...mentioning
confidence: 99%
“…Evidence suggests that adult women and children among Rohingya, are most vulnerable to the COVID-19 due to their misconceptions and lack of awareness regarding the same (16). In contrast, older adults are more susceptible to COVID-19 due to age-related complications (34,35). These factors play an important role in how different groups, especially the most vulnerable within the two communities received information about and responded to the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%